Therapeutic Efficacy of Topical Bay Leaf (Syzygium polyanthum) Extract Gel on Macroscopic Ulcer Healing in Alloxan-Induced Diabetic Rats - Permata Gulo, Elastis; Yunus, Muhammad; Bangar, Roy Indrianto (CV. Nusantara Scientific Medical, 2026)
Diabetes mellitus is a chronic disease that impairs wound healing due to oxidative stress and prolonged inflammation. Bay leaf (Syzygium polyanthum) contains bioactive compounds with potential therapeutic effects in promoting tissue repair. This study aimed to evaluate the effectiveness of topical bay leaf extract gel on macroscopic wound healing in alloxan-induced diabetic rats. This experimental in vivo study used 30 male rats divided into six groups: normal control, negative control, positive control (Bioplacenton), and treatment groups receiving extract gel at concentrations of 2.5%, 5%, and 10%. Diabetes was induced using alloxan, followed by burn wound creation and topical treatment for 14 days. The results showed that treatment groups exhibited faster wound healing compared to the negative control. The 2.5% and 10% extract gel groups demonstrated more optimal wound closure, comparable to the positive control by day 14. These findings indicate that flavonoid and phenolic compounds in bay leaf contribute to antioxidant and anti-inflammatory activities, supporting tissue regeneration. In conclusion, bay leaf extract gel is effective in accelerating wound healing in diabetic conditions. Further studies are recommended to investigate histopathological changes and molecular mechanisms.